Are removal experiments effective tools for assessing plant community resistance and recovery from invasion?. (25th November 2014) - Guido, Anaclara; Pillar, Valério D.; Palmer, Michael
Abstract Removal experiments are useful tools for assessing two important aspects of plant community invasion: (1) resistance to invasion and (2) recovery after invasive species removal. We discuss the potential of such experiments based on a brief systematic review of the literature on community resistance, as measured by invasibility after removal of resident species (reduction of taxonomic/functional richness), and on community recovery, as measured by resident community response after invasive species removal. We found 62 research articles, most of them related to invasive species removal. Few studies used removals to test biotic resistance, despite the importance of resident removals for identifying community components that play key roles in the often‐controversial invasion resistance hypotheses. Furthermore, appropriate experimental controls were rarely used, which would allow separation of the effect of local species extinction from that of disturbance. We hope this review stimulates plant ecologists to adopt removal experiments for studying invasion processes.